Empowering teachers to implement innovative content in physical education through continuous professional development. Issue 2 (15th March 2017) - Braga, Luciana; Jones, Emily; Bulger, Sean; Elliott, Eloise
Abstract : The purpose of this study was to examine teacher perceptions regarding their experiences in a research-informed continuous professional development (CPD) initiative and its influence on their professional readiness to implement innovative content in physical education (PE). Participants included four PE teachers who engaged in a series of hands-on workshops and collaborative activities related to the design and implementation of a mountain biking unit in two middle schools. Qualitative data were collected through post-workshop surveys, semi-structured interviews, and a focus group. Data were analyzed using inductive content analysis, and results revealed four themes: (a) igniting change, (b) transferring to the classroom, (c) student response, and (d) sustaining beyond a single unit. Findings from this study reinforce the need for research-informed CPD efforts in PE and highlight its role in generating a sense of teacher empowerment and promoting systemic change within school-based PE.